Argumentative Techniques in the Holy Qur’an: Surah Al-A‘raf as a Model - zaidi, sana; zaral, salaheddine (El Omda in Linguistics and Discourse Analysis, 2024)
The Holy Quran is an argumentative discourse aimed at influencing opinions and behaviors, presented with miraculous style. Surat Al-A'raf extensively presents the accounts of prophets and addresses monotheism, utilizing various argumentative techniques: connection-based and separation-based.